Early influenza vaccination rates decline in children during the COVID-19 pandemic. Issue 31 (13th July 2021) - Fogel, Benjamin; Schaefer, Eric W.; Hicks, Steven D.
Graphical abstract: Odds of early vaccination in 2020 were 19% lower compared to 2018 (15% lower when adjusted for demographic variables). A model with an interaction term showed increasing odds of vaccination over time for those with private insurance and decreasing odds for those with public insurance. Highlights: Early flu vaccine rates among children declined during the 2020 COVID-19 pandemic. Flu vaccine rates during the pandemic were lower among publicly insured children. Abstract: Background: This investigation sought to determine whether early season rates of pediatric influenza vaccination changed in a season when there was a concurrent COVID-19 pandemic. Methods: This study used cohort and cross sectional data from an academic primary care division in Southcentral Pennsylvania that serves approximately 17, 500 patients across 4 practice sites. Early season (prior to November 1) vaccination rates in 2018, 2019 and 2020 were recorded for children, age 6 months to 17 years. To explore the impact of COVID-19 on vaccination, we fit a model with a logit link (estimated via generalized estimating equations to account for clustering by patient over time) on calendar year, adjusted for race, ethnicity, age, and insurance type. We examined interaction effects of demographic covariates with calendar year. Results: Early vaccination rates were lower in 2020 (29.7%) compared with 2018 and 2019 (34.2% and 33.3%). After adjusting for covariates and accounting for clustering over time, the odds of early vaccination in 2020 were 19% lower compared to 2018 (OR 0.81, 95% CI: 0.78–0.85). In 2020, children with private insurance were more likely to receive early vaccination than in 2018 (OR 1.51, 95% CI: 1.04–1.15), whereas children with public insurance were less likely to receive early vaccination in 2020 than in 2018 (OR 0.62, 95% CI: 1.38–1.65). Conclusions: Early influenza vaccination rates declined in a year with a concurrent COVID-19 pandemic. Modeling that accounts for individual trends and demographic variables identified specific populations with lower odds of early vaccination in 2020. Additional research is needed to investigate whether the COVID-19 pandemic impacted parental intent to obtain the influenza vaccine, or introduced barriers to healthcare access.